Social acceptability of urban air mobility by aircraft category and autonomous phases - PARK, Sun Wook (KDI School, 2021)
Thanks to technology development, air taxis are attracting attention as an opportunity to create a new industry and a solution to traffic congestion in urban areas. Specifically, unmanned, electronic, and autonomous vehicles (AVs) are highlighted as key to modern urban air mobility (UAM). However, some hesitate to use UAM services due to resistance to new technology. Therefore, this study investigated publics’ and experts’ willingness to use UAM services as divided into four phases: traditional helicopters, electric vertical and take-off landing (eVTOL), remotely piloted aviation systems (RPAS), and a fully autonomous system. Results showed public willingness to use was at average 4.6–4.7 points in phases 1–2 and decreases to 3.7–3.8 points in phases 3–4, when using a seven-point Likert scale. Meanwhile, experts’ willingness to use was at average 4.5 points in phase 1, increasing to 5.2–5.7 points in phases 2–4. The differences are statistically significant when using the ANOVA test. Moreover, the independent t-test provided evidence of a gap between experts and the public in willingness to use UAM. Based on the survey, I constructed the regression models based on each phase. Across-phase influential factors were the willingness to pay over 50,000 KRW and the belief that air taxis could be solution to traffic congestion. At phases 1–2, curiosity about the new transportation mode and preference for taking airplane were significant, but they did not affect phases 3–4 due to resistance. The influential factors identified in phases 3–4 were personality as an early adopter and interest in or understanding of the technology. In addition, females were less likely to use UAM due to hesitation to using autonomous system. Based on the analysis results, I interviewed experts in the fields of UAM policy, aviation, and autonomous vehicles. Generally, experts thought it necessary to offer positive information about UAM, increase opportunities to see/learn about UAM, reduce user costs, demonstrate safety, and so forth.
Thesis(Master) -- KDI School: Master of Development Policy, 2021
Keywords: Flying automobiles; Vertically rising aircraft--Economic aspects